Small bowel villous atrophy due to immune-checkpoint inhibitors: report of two cases and literature review - Annalisa Schiepatti; Andrea Premoli; Stiliano Maimaris; Mimma Rizzo; Maria Marples; Laura Villani; Nigel Scott; Federico Sottotetti; David S Sanders; Federico Biagi; Clare Donnellan (BioExcel Publishing Ltd, 2022)
The differential diagnosis of non-coeliac enteropathies (NCEs) is challenging and includes a wide range of aetiologies. Drug-induced NCEs are relatively common and characterized by duodenal villous atrophy, which resolves upon suspension of the offending drug. Immune-checkpoint inhibitors (ICIs), targeting molecules involved in the activation of cytotoxic T cells by targeting, for example, PD-1, PD-L1 and CTLA4, are increasingly used for many types of cancers. Adverse events occurring in the gastrointestinal tract have been described, predominantly in the form of immune-mediated colitis mimicking inflammatory bowel disease. Small bowel involvement whilst on ICI therapy is also possible, though less well described. Herein, we describe two cases of enteropathy with villous atrophy and negative coeliac serology due to ICIs: a 65-year-old man affected by stage IV pulmonary adenocarcinoma under treatment with pembrolizumab and an 18-year-old woman affected by stage IV auricular melanoma who was treated with nivolumab. We also provide a review of the current literature describing small bowel involvement during therapy with ICIs, alone or in combination, for different types of solid tumours. Implications for clinical practice include considering the possibility of small bowel involvement in oncological patients treated with ICIs and the inclusion of ICIs amongst the iatrogenic causes of NCE with villous atrophy. Enteropathies due to ICIs may also represent a pathogenetic model for the understanding of the molecular mechanisms leading to villous atrophy in NCE.